Photo-induced hydrophilicity at the ZnO(112̄0) surface: an evolutionary algorithm-aided density functional theory study - Bao, Shen-Yuan; Li, Dong-Zhi; Gong, Xue-Qing (Physical chemistry chemical physics : PCCP, 2021)
Evolutionary algorithm-aided density functional theory calculations were utilized to determine the stable adsorption structures of H2O at ZnO(112̄0) extensively under different coverages. By decomposing the adsorption energetics, we illustrate that H2O dissociation to a large extent is actually hampered by the barrier for induced distortion of the ZnO surface, and once the surface becomes less difficult to be distorted it will exhibit higher hydrophilicity or even superhydrophilicity. Specifically, photo-stimulation modelling suggests that the surface Zn-O bonds can be weakened by photo-excitation, and the layer of fully dissociated H2O can be then facilitated to form. Accordingly, a novel mechanism for photo-induced superhydrophilicity is proposed.Evolutionary algorithm-aided density functional theory calculations were utilized to determine the stable adsorption structures of H2O at ZnO(112̄0) extensively under different coverages. By decomposing the adsorption energetics, we illustrate that H2O dissociation to a large extent is actually hampered by the barrier for induced distortion of the ZnO surface, and once the surface becomes less difficult to be distorted it will exhibit higher hydrophilicity or even superhydrophilicity. Specifically, photo-stimulation modelling suggests that the surface Zn-O bonds can be weakened by photo-excitation, and the layer of fully dissociated H2O can be then facilitated to form. Accordingly, a novel mechanism for photo-induced superhydrophilicity is proposed.